Implementation Science in Pediatric Critical Care – Sedation and Analgesia Practices as a Case Study - Yang, Youyang; Geva, Alon; Madden, Kate; Mehta, Nilesh M. (Frontiers in Pediatrics, 2022)
Sedation and analgesia (SA) management are essential practices in the pediatric intensive care unit (PICU). Over the past decade, there has been significant interest in optimal SA management strategy, due to reports of the adverse effects of SA medications and their relationship to ICU delirium. We reviewed 13 studies examining SA practices in the PICU over the past decade for the purposes of reporting the study design, outcomes of interest, SA protocols used, strategies for implementation, and the patient-centered outcomes. We highlight the paucity of evidence-base for these practices, and also describe the existing gaps in the intersection of implementation science and SA protocols in the PICU. Future studies would benefit from a focus on effective implementation strategies to introduce and sustain evidence-based SA protocols, as well as novel quasi-experimental study designs that will help determine their impact on relevant clinical outcomes, such as the occurrence of ICU delirium. Adoption of the available evidence-based practices into routine care in the PICU remains challenging. Using SA practice as an example, we illustrate the need for a structured approach to implementation science in pediatric critical care. Key components of successful adoption of evidence-based best practice include, the assessment of the local context: both resources and barriers, followed by a context-specific strategy for implementation, and a focus on sustainability and integration of the practice into the permanent workflow.